Analysis and Evaluation of User Satisfaction using a Combination of Technology Acceptance Model (TAM) and WEBQUAL 4.0 Methods for Website-based Online Information Systems - Tarwoto, Tarwoto; Ma'arifah, Windiya (Program Studi Sistem Informasi Fakultas Teknik dan Ilmu Komputer, 2025)
The advancement of information and communication technology in the era of Industry 4.0 has driven the utilization of the internet, particularly in website-based information systems. This study focuses on evaluating user satisfaction by involving the IT team and analyzing aspects such as usability, accessibility, and the ability to present information on the website amikompurwokerto.ac.id. By adopting the Technology Acceptance Model (TAM) and Webqual 4.0 approaches, this research integrates the results from both methods to improve system quality. The findings reveal a positive relationship between factors such as user attitude, employee satisfaction, individual usage, ease of access perception, and perceived benefits, which influence internet usage intensity. Factors like availability, information quality, and service interaction also influence and significantly impact the improvement of information system quality. This research offers comprehensive insights into user satisfaction evaluation in an academic environment.